Mother's obesity and high child's waist circumference are predictive factors of severe child's obesity: an observational study in French Guiana - Falucar Njuieyon; Emma Cuadro-Alvarez; Elise Martin; Noémie Lachaume; Yajaira Mrsic; Fanny Henaff; Chimène Maniassom; Antoine Defo; Narcisse Elenga (BMC, 2018)
Abstract Background This study aims to describe the predictive factors of severe obesity in children followed in French Guiana. Methods In this observational study, the patients from the French Guianese Childhood Obesity Group database were prospectively included, after giving a statement of patient's non opposition. Results Our group classifications revealed that 36 of 150 (24%) participants were classified as being metabolically abnormal obesity" (MAO), while 114 of 150 (76%) were categorized as metabolically normal obesity" (MNO). MAO-patients were older. Their mothers had more severe obesity. We also observed that their systolic blood pressure was higher. The median Z-score BMI of children with MAO was 4, 9 [4, 05-5, 38], which shows a more obese condition than the MNO group. The median waist-to-height ratio (WTHR) of our study population was high, either 0.63 [0.54-0.59]. No significant differences in the term of pregnancy, father's obesity, gender, birth weight, feeding, diastolic blood pressure and WTHR were found between the two groups. The predictors of MAO status, after adjusting for age and sex, were mother's obesity and high child's waist circumference. Among the comorbidity, there were two Down syndrome, one Cornelia de Lange syndrome, one Nephrotic Syndrome and one Epilepsy. The leptin hormone and insulin levels were higher in MAO than in MNO, while 25-OH D-vitamin was higher in MNO. Conclusion This study indicates the need to incorporate waist circumference into routine clinical practice, in addition to traditional measures of weight, height, body mass index and waist-to-height ratio.